Gilbert Weather Bureau (Meteorology) for Boys - Gilbert, A. C. (Alfred Carlton), 1884-1961 (Salt Lake City, UT : Project Gutenberg, 2022)
"Gilbert Weather Bureau (Meteorology) for Boys" by A. C. Gilbert is a scientific publication written in the early 20th century. The book aims to educate young readers about the principles of meteorology and the science behind weather prediction, emphasizing the importance of understanding atmospheric phenomena. Through practical experiments and explanations, it seeks to demystify weather forecasting and encourage curiosity about the natural world. The opening of this work introduces readers to the concept that weather is not random but rather governed by consistent scientific laws. It dispels common misconceptions about the unpredictability of weather and highlights the role of meteorologists as scientists rather than mystics. Gilbert emphasizes the value of setting up a personal Weather Bureau station to observe atmospheric conditions and provides a variety of experiments to demonstrate fundamental scientific concepts related to air, weather patterns, and the tools used for measurement. Overall, this introduction lays the groundwork for a comprehensive understanding of meteorological principles and experiments that follow. (This is an automatically generated summary.)
Release date is 2022-02-13
Richard Tonsing, Juliet Sutherland and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Meteorology -- Juvenile literature; Weather -- Juvenile literature; Meteorology -- Problems, exercises, etc